Analisis Transparansi Jabatan Dan Dampaknya Terhadap Semangat Dan Kinerja Karyawan - Hani Ayu Lestari; Achmad Zamroni; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Transparency in a company is needed and important for the smooth running of the company. A team will achieve success if it can apply a management system which consists of four stages, namely planning/planning, managing/organizing, implementing/actuating, supervising/controlling. With the running of the system in accordance with these stages, it can be ascertained that the company will run according to the policies that have been set by the company. And will affect employee morale and performance in accordance with company expectations. There are many work systems in a company, one of which is the foreman system, where the foreman's job is to carry out the stages of the management system so that it will affect the performance of his subordinates, because the strength of subordinates will be formed by the presence of leaders who have good quality and quantity and have broad insight. to be able to solve the problems that will be encountered.